Prevalence of asymptomatic non-falciparum and falciparum malaria in the 2014-15 Rwanda Demographic Health Survey - Claudia Gaither; Camille Morgan; Rebecca Kirby; Corine Karema; Pierre Gashema; Jenna Zuromski; Samuel J. White; Hillary M. Topazian; David Giesbrecht; Kyaw Thwai; Neeva Wernsman Young; Varun Goel; et al. (PLoS ONE, 2025)
Background Recent molecular surveillance suggests an unexpectedly high prevalence of non-falciparum malaria in Africa. Malaria control is also challenged by undetected asymptomatic P. falciparum malaria resulting in an undetectable reservoir for potential transmission. Context-specific surveillance of asymptomatic P. falciparum and non-falciparum species is needed to properly inform malaria control programs. Methods We performed quantitative real time PCR for four malaria species in 5,050 primarily adult individuals in Rwanda using the 2014–2015 Demographic Health Survey. We assessed correlates of infection by species to explore attributes associated with each species. Asymptomatic P. ovale spp., P. malariae, and P. falciparum malaria infection had broad spatial distribution across Rwanda. P. vivax infection was rare. Results Overall infection prevalence was 22.3% (95%CI [20.3, 24.3]), with P. falciparum and non-falciparum at 16.3% [14.5, 18.1] and 8.0% [6.6, 9.3], respectively. Parasitemias tended to be low and mixed species infections were common, especially where malaria transmission and overall prevalence was the highest. P. falciparum infection was associated with lower wealth, rural residence and low elevation. Fewer factors were significantly associated with non-falciparum malaria. Conclusions Asymptomatic non-falciparum malaria and P. falciparum malaria are common and widely distributed across Rwanda in adults. Continued molecular monitoring, preferably done by the national malaria control program, of Plasmodium diversity using routine survey samples is needed to strengthen malaria control.